On solvability of the matrix equation AXB = C over a principal ideal domain - Prokip, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
In this paper we present conditions of solvability of the matrix equation AXB = B over a principal ideal domain. The necessary and sufficient conditions of solvability of equation AXB = B in term of the Smith normal forms and in term of the Hermi-te normal forms of matrices constructed in a certain way by using the coefficients of this equation are proposed. If a solution of this equation exists we propose the method for its construction.